A Comparative Analytical Study of Functional and Esthetic Outcomes of Infraorbital and Subciliary Incisions to Assess the Redundancy of the Infraorbital Approach - Jefferson Prince; Premalatha Shetty; Arvind Ramanathan; Srikant N. (The Scientific World Journal)
Conclusions: The infraorbital approach has low esthetic and functional complications of scleral show and ectropion with relatively good esthetics and ease of performing for infraorbital and orbital floor fractures.